High-dimensional genomic data bias correction and data integration using MANCIE - Chongzhi Zang (Nature Portfolio, 2016)
Analyses of data from high-throughput genomic technologies are challenging given large data dimensionality. Here, Liu and colleagues describe a method called MANCIE (Matrix Analysis and Normalization by Concordant Information Enhancement) that can conduct genomic data normalization and bias correction to detect biologically relevant information.